2011
DOI: 10.3109/0886022x.2011.565137
|View full text |Cite
|
Sign up to set email alerts
|

Acute Kidney Injury due to Rhabdomyolysis in H1N1 Influenza Infection

Abstract: Acute kidney injury (AKI) is rarely reported in the clinical course of H1N1 infection and this condition is strongly related with increasing of mortality risk. However, there are no sufficient data about the development of AKI due to H1N1 infections. The recent reports were documented for elevation of creatinine phosphokinase levels in the course of influenza infection, but rhabdomyolysis was rarely reported. Herein, we present a 28-year-old female patient and a 19-year-old male patient with AKI in the course … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 11 publications
1
10
0
Order By: Relevance
“…There have been approximately 27 reported cases of rhabdomyolysis in the setting of influenza infection, although this likely represents a small fraction of the total cases as myositis and/or rhabdomyolysis have infrequently been reported prior to the 2009 A(H1N1) pandemic (Table ) . Among 18 patients in Mexico with influenza A(H1N1)pdm09 infection, 62% of patients had mild‐to‐moderate elevations of creatinine kinase (CK) .…”
Section: Resultsmentioning
confidence: 99%
“…There have been approximately 27 reported cases of rhabdomyolysis in the setting of influenza infection, although this likely represents a small fraction of the total cases as myositis and/or rhabdomyolysis have infrequently been reported prior to the 2009 A(H1N1) pandemic (Table ) . Among 18 patients in Mexico with influenza A(H1N1)pdm09 infection, 62% of patients had mild‐to‐moderate elevations of creatinine kinase (CK) .…”
Section: Resultsmentioning
confidence: 99%
“…Elevated creatine kinase (CK) has been implicated as a contributing factor for AKI in pH1N1 [14,17,22,28]. Pettila et al reported that 15.8% of AKI patients had CK levels exceeding 5000 IU/L and found a trend of increasing CK levels with worsening AKI [26].…”
Section: Discussionmentioning
confidence: 99%
“…AKI commonly accompanies critical illness and independently increases risks of death, prolonged length of stay, and development of new chronic kidney disease (CKD) among survivors [11,12]. Recently, reports have described the incidence and outcomes of AKI among critically ill adult and pediatric pH1N1 patients [13]–[28]. Many studies, however, were limited by design (case reports [14,17,20,22,24,28] or small case series [13,15,18,21,27]), small sample size [16,19,25], or single-center enrollment [13,15,16,18,21].…”
Section: Introductionmentioning
confidence: 99%
“…However, many clinicians may fail to recognize rhabdomyolysis as an important complication associated with influenza A/H1N1 2009. Recently, several adult cases of severe rhabdomyolysis and acute renal failure associated with influenza A/H1N1 2009 were reported 2–4 . We report herein a pediatric case involving rhabdomyolysis and compartment syndrome associated with influenza A/H1N1 2009.…”
mentioning
confidence: 84%
“…Recently, several adult cases of severe rhabdomyolysis and acute renal failure associated with influenza A/H1N1 2009 were reported. [2][3][4] We report herein a pediatric case involving rhabdomyolysis and compartment syndrome associated with influenza A/H1N1 2009.…”
mentioning
confidence: 98%